PEMBAGIAN HARTA WARIS DENGAN WASIAT (PENDEKATAN USHUL FIQIH) - Purkon, Arip (JURNAL ILMU SYARIAH, 2014)
A Hidden Inheritance With the Probate Division (Usul Fiqh Approach). In Islamic law, the division of the estate (faraidh) is part of theproblem is already clear rules (qat'i al-dilalah). However, there are still a few people who questioned aspects of justice in this faraidh problem. One solution to bridge this is the concept of testament. The division of property by testamentary relatively more flexible than those specified in the science faraidh. However, will still not be separated from the legal rules that have been set Qur'an and Sunnah.